1976
DOI: 10.1002/1097-0142(197604)37:4<1737::aid-cncr2820370419>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic cystosarcoma phyllodes.A light and electron microscopic study

Abstract: Two cases of metastatic cystosarcoma phyllodes, one in lung and the other in axillary lymph nodes, were studied with the light and the electron microscopes. The malignant element of these tumors appears to be a poorly differentiated mesenchymal cell. No evidence supporting the presence of epithelial cells was found. The tumor metastatic to the axilla exhibited intracellular virus‐like particles similar to those described in adenocarcinoma of breast and other sarcomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…In fact, only the stromal cells potentiate to metastasise. 26 Unlike phyllodes tumours, fibroadenomas have a true capsule. According to Azzopardi and Salvadori, they had proposed a widely acceptable definitions for phyllodes tumour between benign, borderline and malignant type.…”
Section: Diagnosismentioning
confidence: 99%
“…In fact, only the stromal cells potentiate to metastasise. 26 Unlike phyllodes tumours, fibroadenomas have a true capsule. According to Azzopardi and Salvadori, they had proposed a widely acceptable definitions for phyllodes tumour between benign, borderline and malignant type.…”
Section: Diagnosismentioning
confidence: 99%
“…The stroma is the neoplastic component and determines the pathological behaviour 49. Only the stromal cells have the potential to metastasise 50. Primary tumours of the breast with pure sarcomatous differentiation and the absence of epithelial elements should be regarded as soft tissue sarcomas 51…”
Section: Pathologymentioning
confidence: 99%
“…Distant disease has appeared as early as at the time of initial therapy or as late as 12 years [4], and it is believed that the hematogenous route is responsible for this tumor dissemination. It is extremely rare for the regional lymphatics to be involved [4,14]. In the present report, the patient presented 1 year after initial therapy with a solitary mandible lesion and accompanying trismus and pain.…”
Section: Discussionmentioning
confidence: 97%
“…Except for some notable exceptions, the treatment of metastatic disease has been disappointing [4]. Fernandez et al [14] reported a single case in which a lung metastasis was resected 6 years following the initial diagnosis of CP; however, the final outcome in this patient was not…”
Section: Discussionmentioning
confidence: 99%